MANAGEMENT OF A RARE CASE OF PEDIATRIC DEEP STERNAL WOUND INFECTION WITH VACUUM-ASSISTED CLOSURE (VAC) - Rianto Noviady Ramli; Ayu Prima Kusumaputri; Arif Yudho Prabowo; Yunanto Kurnia; Almas Nur Prawoto (Jurnal Rekonstruksi dan Estetik)
HIGHLIGHTS: